Not ordinary men : the story of the Battle of Kohima - Colvin, John. (London : L. Cooper, 1995)
"Having driven the British and Indian Forces out of Burma in 1942, General Mutaguchi, Commanding the 15th Japanese Army, was obsessed by the conquest of India. In 1944 the British 14th Army, under its commander General Slim, drew back to the Imphal Plain before Mutaguchi's impending offensive. However to the north, the entire Japanese 31st Division had crossed the Chindwin and, on April 5, arrived at the hill-station and road junction of Kohima, cutting off Imphal except by air from the supply point at Dimpapur. Kohima was initially manned by only 266 men of the Assam Regiment and a few hundred convalescents and administrative troops. They were joined, on April 5, by 440 men of the Fourth Battalion of the Royal West Kent Regiment, straight from the Battle of Arakan. In pouring rain, under continual bombardment, this tiny garrison held the assaults of thirteen thousand Japanese troops in hand-to-hand combat for sixteen days, an action described by Mountbatten as 'probably one of the greatest battles in history in effect the Battle of Burma, naked, unparalled herosim, the British/Indian Thermopylae'. Book jacket."--Jacket.
I. The Japanese Screen -- II. The Road to Kohima -- III. Japanese Intentions and Order of Battle -- IV. The Curtain-Raiser at Sangshak -- V. The Nagas and Others -- VI. The Assam Regiment into Battle -- VII. The Assam Regiment: Jessami, Kharasom, Phek -- VIII. On the Eve of the Storm -- IX. Kohima: The Neglected Garrison -- X. The Royal West Kent Regiment Arrives -- XI. Colonel Laverty's Dispositions and the Tactical Doctor -- XII. The Assault on Detail Hill -- XIII. The Last Easter of Lance-Corporal Harman -- XIV. Not Good, Anywhere ... -- XV. Supply Hill Holds, Just ... -- XVI. 'The Black 13th' -- XVII. The First Assam Take Over -- XVIII. The Garrison Relieved -- XIX. Meanwhile, Outside ... -- XX. The Outlook for General Sato -- XXI. The Ridge -- XXII. Advance to Naga Village -- XXIII. The Assault on Naga Village -- XXIV. Death Valley -- XXV. The Ridge Again -- XXVI. Lieutenant-General Sato versus General Mutaguchi -- XXVII. The Japanese Hold the Bunkers, but the Tennis Court Falls -- XXVIII. Derek Horsford takes Point 5120 -- XXIX. The Japanese leave Aradura Spur -- XXX. General Sato goes Home -- XXXI. IV and XXXIII Corps Meet -- Envoi.
Includes bibliographical references (pages 239-243) and index.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- Burma; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Birmanie; Military campaigns; Kohima, Battle of, Kohima, India, 1944.; Burma; India -- Kohima; History (Second World War); Kohima, Battle of, Kohima, India, 1944; World War, 1939-1945 -- Campaigns -- Burma; war fiction